Influence of a Teaching Module on Adolescent Girls' Understanding and Perception of Early Menarche - Rakkini L, Motcha; Hema, V.H (Salud, Ciencia y Tecnología, 2023)
The commencement of menarche, which signifies the first occurrence of menstrual bleeding, holds considerable importance in the lives of young girls going through adolescence. This research aimed to evaluate the influence of a Teaching module on the understanding and outlook pertaining to early menarche in adolescent girls. Employing a quantitative research design, a sample of 300 participants was chosen using uncomplicated random selection methods. The investigation employed a structured knowledge questionnaire and a five-point rating system to assess participants' comprehension and perception. The experimental group initially perceived early menarche moderately (68 %). Results from their first assessment indicated 45,3 % lacked sufficient knowledge, 42,7 % had moderately acceptable knowledge, and 12 % demonstrated satisfactory knowledge. Impressively, the subsequent evaluation showed a substantial improvement, with 97,3 % now possessing adequate knowledge, and only 2,7 % retaining moderately acceptable knowledge. Conversely, the control group's initial review displayed 83,3 % inadequate knowledge and 16,7 % moderately acceptable knowledge. Following the intervention, the control group had 72,7 % maintaining insufficient knowledge and 26,7 % displaying moderate perception. 32 % have a favorable perception. Post-module, 92 % showed a good perception, 8 % remained moderate. The module effectively enhanced knowledge and perception on early menarche. This study underscores the pivotal role of targeted educational interventions in amplifying knowledge and perception concerning early menarche. The outcomes highlight the potential benefits of such interventions in equipping adolescent girls with essential information and awareness to navigate this transformative phase in their lives effectively